2021
DOI: 10.14423/smj.0000000000001263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SARS-CoV-2 on the Practice of Otolaryngology

Abstract: Objectives: Otolaryngologists in Texas have been greatly affected by the coronavirus disease 2019 (COVID-19) pandemic. Executive orders and professional recommendations have changed the way otolaryngologists practice. The objective of the study was to determine the effect of COVID-19 on otolaryngologists in the state of Texas.Methods: We surveyed the Texas Association of Otolaryngology to evaluate burnout, research output, and ability to respond to the pandemic. We also looked at the effect of Texas government… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…Momin et al ( n = 38) found that a common stressor among otolaryngologists was an inability to meet their patients' needs. 10 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Momin et al ( n = 38) found that a common stressor among otolaryngologists was an inability to meet their patients' needs. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Otolaryngologists also faced patient‐care challenges with the suspension of elective procedures at the start of the pandemic. Momin et al ( n = 38) found that a common stressor among otolaryngologists was an inability to meet their patients' needs 10 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations